A Single-Input Single-Output Approach by using Minor-Loop Voltage Feedback Compensation with Modified SPWM Technique for Three-Phase AC–DC Buck Converter - Alias, Azrita (Korean Institute of Power Electronics, 2013)
The modified sinusoidal pulse-width modulation (SPWM) is one of the PWM techniques used in three-phase AC–DC buck converters. The modified SPWM works without the current sensor (the converter is current sensorless), improves production of sinusoidal AC current, enables obtainment of near-unity power factor, and controls output voltage through modulation gain (ranging from 0 to 1). The main problem of the modified SPWM is the huge starting current and voltage (during transient) that results from a large step change from the reference voltage. When the load changes, the output voltage significantly drops (through switching losses and non-ideal converter elements). The single-input single-output (SISO) approach with minor-loop voltage feedback controller presented here overcomes this problem. This approach is created on a theoretical linear model and verified by discrete-model simulation on MATLAB/Simulink. The capability and effectiveness of the SISO approach in compensating start-up current/voltage and in achieving zero steady-state error were tested for transient cases with step-changed load and step-changed reference voltage for linear and non-linear loads. Tests were done to analyze the transient performance against various controller gains. An experiment prototype was also developed for verification.